Bioactivities of plant extracts collected in Halmahera, Indonesia: A bioprospection study of underexplored plant species - Marlin Megalestin Raunsai; Kartika Dyah Palupi; Ahmad Fathoni; Andria Agusta (Universitas Gadjah Mada, 2021)
The discovery of new antibiotics to overcome the growing resistance problem as well as the discovery of new natural, safe antioxidants to combat oxidative stress are still urgently needed. Medicinal plants are known to produce potential therapeutic substances which are more biologically selective than synthetic compounds. Therefore, we explored the bioactivities of 35 ethanolic extracts from 24 underexplored plant species collected in Halmahera, to find potential sources for antibacterial and antioxidant agents.  Dried plant parts were extracted using ethanol 96%. Thin layer chromatography-direct-bioautography (TLC-DB) and minimum inhibitory concentration (MIC) determination were used to evaluate the antibacterial effect. Antioxidant activity was determined against DPPH using TLC-DB and microdilution assay. Total phenolic content (TPC) was determined using Folin-Ciocalteu's method. The ethanolic extracts exhibited moderate to weak antibacterial activity against Escherichia coli and Staphylococcus aureus. However, the leaf extract of Elaeocarpus dolichostylus, Elaeocarpus multiflorus, and Psychotria celebica as well as the stem bark extract of Elaeocarpus dolichostylus, Cinnamomum sintoc, and Garcinia latissima displayed very strong antioxidant activities against DPPH with AAI values between 4.60 to 13.42. A strong correlation between TPC and antioxidant activity with r = 0.8712 was observed. Despite the moderate to weak antibacterial activity, eight underexplored plant species exhibit strong antioxidant activities. A high correlation between TPC and antioxidant activity indicating a prominent role of phenolic compounds in the plants' antioxidant properties. These findings indicate that collected plants from Halmahera are potential to be studied and developed further as the potential sources for novel antioxidants.